The Future of Sovereign Borrowing in Europe - Morten Balling; Ernest Gnan; Johannes Holler; Ulrich Bindseil; Nicolas Sauter; Hans J. Blommestein; Maria Cannata; Juha Kilponen; Alessandro Missale; Ewald Nowotny; Guido Sandleris; Mark L.J. Wright (SUERF - The European Money and Finance Forum, 2013)
In March 2013 around 130 participants from academia, banking and finance, governments and central banking gathered at the premises of the OeNB in Vienna for a conference jointly organized by the European Money and Finance Forum SUERF, the OeNB and the Austrian Society for Bank Research to discuss “The Future of Sovereign Borrowing.” The financial, economic and sovereign debt crisis has fundamentally changed the rules of the game in sovereign debt markets, particularly in the euro area, but also beyond its borders. Sovereign bonds are no longer widely perceived as `risk-free' assets. Even the sovereign bonds of safe-haven countries have come under close scrutiny or lost some of their prime ratings. Yet crisis countries have seen dramatic downgrades of their sovereign debt ratings so that they face soaring risk spreads and unsustainably high financing costs (or even a loss of access to bond market financing), pushing them towards shorter financing or forcing them to rely on financial support from other countries and the international community or massive intervention by central banks.
Keywords: E42; E52; E58; E62; E63; F34; H12; H63; 330; fiscal policy; monetary policy; sovereign bond markets; sovereign debt; monetary union; financial stability; sovereign yield spreads; sovereign debt crisis; crisis resolution mechanisms; debt sustainability; sovereign borrowing; funding strategies; public debt management; Euro Area debt crisis; sovereign risk; crisis resolution mechanisms; government debt; monetary policy implementation; international comparison; risk management; GDP-Indexed Bonds; Argentinian debt crisis; inflation indexation; real indexation; Internationale Staatsschulden; Länderrisiko; Schuldenkrise; Schuldenmanagement; Europa